Sejarah Islam Di Maroko - Azhar Nur (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2011)
Islam came to Marocco on 638 A.D. brought by Musa bin Nusair as the al-Walid bin Abdul Malik (Umayaah Dynasty). Marocco applied monarch system dwelled by most 98% of Moslem population. Marocco had important roles in Islamic history, mainly in spreading Islam in South Africa region and this nation became the gateway of Islam invasion to Spain, even to Asia. Long history of Marocco, from dynasty to other dynasties has specific history which coloures Islamic progress. There were Adrisid, Murabitun, and Muwahhidun dynasty which has great roles in spreading Islam.